New Arabic Stemming based on Arabic Patterns - Mohammed , Rafea (Iraqi Journal of Science, 2022)
Algorithms for Arabic stemming available in two main types which are root-based approach and stem-based approach. Both types have problems which have been solved in the proposed stemmer which combined rules of both main types and based on Arabic patterns (Tafealat1) to find the added letters. The proposed stemmer achieved root exploration ratio (99.08) and fault ratio (0.9).